The Religious Practises of Deaf Muslims in Malaysia: A Case Study at the Special Education School - Nizaita, Omar; Abd Hakim, Mohad; Ros Aiza, Mohd Mokhtar (2018)
The religious practice in everyday life is part of the manifestation of religion and belief of every human being. Within the Islamic context, for example, religious practices must be one that stems from the Islamic religious laws. All Muslims, including the deaf, need to perform their religious obligations within their abilities. However, not much attention is given to people with disability, such as the deaf, with regards to observing their religious practices and in understanding the related problems that they face. This article serves to explain religious practices of the deaf Muslims through a research conducted at a Special Education School (for the Deaf) in Kota Kinabalu, Sabah and the Activity Centre, Society for the Welfare of the Deaf in Terengganu, Malaysia. This study employs the survey method, which uses the questionnaire as an instrument for data collection. Among the aspects of religious practices observed are acts of worship like prayer and fasting, as well as general practices like eating habits, and ways of dressing. The study showed that the hearing impaired also perform religious practices in their daily life, although a majority of them are unable to perform them completely.